2013
DOI: 10.5114/aoms.2013.34574
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of cardiac hemodynamics in patients with advanced cancer and with chronic heart failure: a pilot feasibility study

Abstract: IntroductionRelationships between cardiac pressure and volume have been suggested as markers of cardiac contractility; parameters include stroke work and the maximal rate of pressure rise during isovolumic contraction (dP/dtmax). Patients with cancer often display dyspnea and fatigue. These are also frequent symptoms in patients with chronic heart failure (HF). The reasons for similar symptoms in cancer patients are unknown. Using the novel Nexfin Finapres technique, we sought to assess measures of cardiac per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…Other organs also waste, however, including cardiac muscle and adipose tissue, two organs that clearly play an important role in cachexia and pancreatic cancer outcomes. [55][56][57][58][59] Here, we observed wasting of skeletal muscle, heart, fat, and multiple other organs, as well as activin induction in most of those organs. Mice with skeletal muscle-specific activin inhibition here showed preserved body weight with both activin low and activin high tumours but did not show prolonged survival, unlike WT mice bearing the same activin low tumours and treated with ACVR2B/Fc.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Other organs also waste, however, including cardiac muscle and adipose tissue, two organs that clearly play an important role in cachexia and pancreatic cancer outcomes. [55][56][57][58][59] Here, we observed wasting of skeletal muscle, heart, fat, and multiple other organs, as well as activin induction in most of those organs. Mice with skeletal muscle-specific activin inhibition here showed preserved body weight with both activin low and activin high tumours but did not show prolonged survival, unlike WT mice bearing the same activin low tumours and treated with ACVR2B/Fc.…”
Section: Discussionmentioning
confidence: 64%
“…Muscle represents more than 40% of body weight, and thus, its wasting accounts for a large part of body weight loss in cachexia. Other organs also waste, however, including cardiac muscle and adipose tissue, two organs that clearly play an important role in cachexia and pancreatic cancer outcomes . Here, we observed wasting of skeletal muscle, heart, fat, and multiple other organs, as well as activin induction in most of those organs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiac output was observed in patients with cancer, and in rats, a slight increase in cardiac function was noted in early stages of cancer 12,32. This could, in part, be responsible for a transient rise in propranolol and iohexol clearance on D5.…”
Section: Discussionmentioning
confidence: 98%
“…Increased cardiac output was observed in patients with cancer, and in rats, a slight increase in cardiac function was noted in early stages of cancer. 12,32 This could, in part, be responsible for a transient rise in propranolol and iohexol clearance on D5. On the other hand, cardiac function was shown to be severely impaired in cancer cachexia 12 and could contribute to decreased renal and hepatic blood flow thereby affecting propranolol and iohexol elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group has shown that patients with colorectal cancer demonstrate reduced exercise capacity as assessed by spiroergometry and that mildly, but significantly reduced LVEF, reduced heart rate variability, and reduced lean mass may be pathophysiologically important . In addition, cancer patients tend to present with higher cardiac output and a maximal rate of pressure rise during an isovolumic contraction than healthy control subjects, possibly adding additional stress to cardiac function in cancer . In patients with cardiovascular disease, we know that an elevated resting heart rate is a valid marker of all‐cause mortality as well as for outcomes in cardiac rehabilitation .…”
Section: Introductionmentioning
confidence: 99%